Investigation of the effects of Kahramanmaraş earthquake series on Cyprus Arc, Dead Sea fault, Hatay regions and stations close to two earthquakes epicenters - Pırtı, Atınç (Geodesy and Cartography, 2024)
In various parts of the globe, there have been several earthquakes of a modest size. Monitoring the change of the points over time is a key component of typical techniques for extracting dynamic responses. This technique was unable to completely extract all of the earthquake’s dynamic properties. The GNSS precise point positioning (PPP) may be a useful tool for obtaining values of the point’s displacement that are more exact up to millimeters, which can help to overcome these flaws and evaluate the seismic wave of such earthquakes. Ultimately, PPP is a crucial tool for getting the precise observations. In this study, Canadian Spatial Reference System Precise Point Positioning (CSRS-PPP) approach to analyze the station’s displacement components and the station’s heights in periods from the two Kahramanmaraş earthquakes. The earthquake sequences that occurred in Turkey’s Kahramanmaraş in 2023 is an example of complicated faulting brought on by interactions between three plates close to the Hatay Triple Junction (HTJ). While the relative plate movements in this area are minimal (usually less than 10 mm/year), even sluggish plate motion zones may nevertheless see earthquakes that are quite destructive. Due to the three-plate system’s unusual geometry, a number of large earthquakes with very varied fault orientations were active throughout this series. A 7.8-magnitude earthquake happened on February 6, 2023 in southern Turkey, close to Syria’s northern border. A magnitude 7.5 earthquake, situated about 95 kilometers to the southwest, was occurred nine hours after the first one. The first earthquake was as big as the most powerful one ever recorded there in 1939 and was the most catastrophic to strike earthquake-prone Turkey in more than 20 years. In this study, the effects of two earthquakes in Kahramanmaraş were investigated on the Cyprus Arc, the Dead Sea fault, Hatay and the points close to two earthquakes zone. In the obtained results, it was computed that the greatest horizontal displacement occurred at the HAT2 station with 68.97 cm.